Use of the Different Polyacrylamide Gel Electrophoresis (PAGE) Methods in the Characterization of Human Pathogenic Staphylococcus aureus Strains - Berber, Ismet; Alan, Negmetullah; Ekin, Suat; Onlu, Harun (Asian Journal of Chemistry, 2010)
In the study, a total of 41 strains of Staphylococcus aureus including 38 clinical isolates and 3 reference strains were characterized according to biotyping, plasmid profiles and the numerical analysis of the protein profiles. The antibiogram results showed that the isolates were resistant against the tested antibiotics, except for vancomycin. Furthermore, plasmid profile analysis confirmed that the strains consisted of only one plasmid. Present findings indicated that the whole-cell and extracellular protein profiles obtained by using SDS-PAGE methods to be good typing tool for the differentiation of S. aureus strains at the species level, not strain level. However, Native-PAGE of whole-cell proteins was the most reliable and rapid method for differentiation between MRSA and ordinary S. aureus strains comparing to other applying PAGE techniques. In addition, it was determined that the same clone was responsible for most cases of MRSA and other S. aureus epidemic among surveyed hospitals. In concl-usion, this study supposed that together application at least two different polyacrylamide gel electrophoresis (PAGE) techniques can be offer accurate and an effective approach to the investigation of taxonomic relationships within human pathogenic S. aureus strains.